Qualitative systematic review of the acceptability, feasibility, barriers, facilitators and perceived utility of using physical activity in the reduction of and abstinence from alcohol and other drug use. (October 2020) - Horrell, J.; Thompson, T.P.; Taylor, A.H.; Neale, J.; Husk, K.; Wanner, A.; Creanor, S.; Wei, Y.; Kandiyali, R.; Sinclair, J.; Nasser, M.; Wallace, G.
Abstract: Given the growing global increase in harm from alcohol and substance use, and the inadequacy of standard treatment to tackle the challenge, the use of physical activity (PA) interventions has received increased attention. The aim of this review is to identify common and cross cutting themes relating to how and why physical activity may impact on reduction of/abstinence from alcohol and other drug use to support future intervention design (including aspects of physical activity, barriers and facilitators, and elements of support which may have an impact). Twenty papers including qualitative data were included in the synthesis. A deductive coding framework was created and sought to identify biological, environmental and psycho-social barriers, facilitators and mechanisms of participants' experience of engaging with physical activity interventions. Key themes supported in the evidence included how interventions influence use (e.g. reduced cravings, increases in bodily awareness and health and fitness, the development of positive focus and new identity, and increases in mood and quality of life); the impact of frequency, intensity, type, duration and timing of physical activity; perceived barriers and facilitators to engaging in physical activity (e.g. health and fitness, access and affordability, perceptions of others); and details of how much support and in what form best supports sustained changes in physical activity (e.g. social support and environment). Despite evidence being sparse, key barriers and facilitators pertinent to intervention design were identified. Recommendations for future research are indicated and the evidence promotes the need for individually tailored programmes of support for physical activity. Highlights: A comprehensive qualitative review of physical activity for alcohol and/or substance use. Identifies acceptable and effective components. Categorizes common themes across a variety of interventions. Makes recommendations for designing and delivering interventions.